Systemic inflammation among adults with diagnosed and undiagnosed cardiometabolic conditions: a potential missed opportunity for cardiovascular disease prevention - Mainous, Arch G.; Sharma, Pooja; Jo, Ara (Frontiers in Medicine, 2024)
Context Systemic inflammation is associated with cardiovascular morbidity and mortality. Since inflammation is not screened in the population, the prevalence, particularly among individuals with undiagnosed cardiometabolic disease, is unclear. Objective To assess the prevalence of elevated inflammation using high sensitivity C-reactive protein (hs-CRP) (>0.30 mg/dL) in adults with no cardiometabolic disease, undiagnosed disease and diagnosed disease. Methods We conducted a cross-sectional analysis of the 2015–2020 National Health and Nutrition Examination Survey which allows for population estimates of the US population. Adults > = 20 years old were included. HsCRP levels >0.30 mg/dL represented inflammation. Individuals were classified into disease defined as having one or more of the following: diagnosed disease–diabetes, hypertension, hyperlipidemia, or obesity by diagnosis; undiagnosed disease (self-report of no doctor diagnosis but positive biomarker); no disease. Results 12,946 unweighted individuals representing 315,354,183 adults in the US population were assessed. The proportion of adults with systemic inflammation is 34.63%. The proportion of individuals aged 20 years and older with no disease, undiagnosed disease and diagnosed disease and inflammation was 15.1, 29.1 and 41.8%, respectively. When stratifying by race/ethnicity among individuals with elevated inflammation Non-Hispanic Black people have the highest prevalence (50.35%) in individuals with diagnosed disease followed by Hispanics (46.13%) and Non-Hispanic White people (40.15%) (p < 0.01). In logistic regressions adjusted for sociodemographic variables, individuals with undiagnosed cardiometabolic disease have an increased risk of elevated inflammation as measured by CRP (OR 2.38; 95%CI = 1.90–2.99). Conclusion In conclusion, a substantial proportion of the adult population, particularly minority and low socioeconomic populations, have elevated inflammation. Systemic inflammation may be a potential focus for disease prevention and disease progression in primary care.